Micoherbicida asociado a la mancha foliar de Chenopodium album L. - Sánchez-Arizpe, Abiel; Departamento de Parasitología, Universidad Autónoma Agraria Antonio Narro, Antonio Narro #1923, C.P. 25315, Buenavista, Saltillo, Coahuila. (2020)
The objective this research was identify the fungi associated with the Chenopodium album leaf spot. Samplings were carried out at Universidad Autonoma Agrarian Antonio Narro in a manner directed towards the weeds (10 plants) that showed signs and symptoms of this disease (pycnidia and a yellow halo on the leaves) and were later taken to the phytopathology laboratory for isolation and identification. The weed identified by morphological criteria. Pathogen was identified by morphocultural of 100 conidia criteria using AxioVision Release 4.5 software. The purification of the isolates was performed by hypha tip in PDA. Macrophoma sp. was identified damaging the weed C. album whit conidia ellipsoidal to subglobose, of 18.21 µm length and 2.56 µm width. Therefore a future investigation of this pathogen and host is recommended.